REVITALISASI LEGENDA PANCUR KUTA MELALUI PERANCANGAN KOMIK DIGITAL - Mayang Savira; Dyla Nur Afriana; Dian Syahfitri (Jurnal Education and Development, 2022)
The legend of Pancur Kuta is a legend originating from Talun Kenas Village in Deli Serdang Regency. The origin of Pancur Kuta tells about a shower that is believed by local residents to protect the village from disaster. This legend is not widely known by the public. Therefore, through digital comics, legends can be developed with new creativity and innovations so that people are more captivated, especially among children. In this study, qualitative methods were used to find out information about the Pancur Kuta story. This research is retold with the concept of comic media as an effort to unite the stories and fantasies of readers and cultivate the preservation of folklore, especially legends. Comic storytelling is packaged in the form of narration and illustrations to make it easier for readers to access them through their gadgets. The application of this comic media in digital form.